Photon counting in stellar intensity interferometry: current status and future prospects - Horch, Elliott P. (Advanced Photon Counting Techniques XIX, 2025)
Intensity interferometry, also known as the Hanbury Brown and Twiss effect, has seen significant interest in astronomy in recent years. The method involves recording timing correlations between photons received at two or more telescopes in order to derive extremely high spatial resolution information about an astronomical object, potentially including imaging stellar surfaces and other objects at unprecedented scales. This paper will briefly review the technique, discuss the performance characteristics of the of photon counters used in modern intensity interferometers, and describe opportunities for the future. As an example of photon counting with a working instrument, observing experiences with the Southern Connecticut Stellar Interferometer (SCSI), a three-station instrument using single-photon avalanche diode (SPAD) detectors, will be described. The recent lessons learned with this and other instruments in use today give a clear picture of the next steps needed to upgrade efficiency and successfully observe fainter objects. If successful, these improvements would provide a strong argument for creating situations where intensity interferometers can have baselines of one to several kilometers, which would unlock the spatial detail needed to address several exciting astrophysical questions.
Keywords: Astronomy; Current (fluid); Intensity (physics); Interferometry; Optics; Photon; Photon counting; Physics; dept.phy

Speckle Interferometers - Horch, Elliott P. (The WSPC Handbook of Astronomical Instrumentation, 2021)
Keywords: dept.phy

Mapping the Orbits of K Dwarf Multiples as a Part of RECONS - Lesley, D. Xavier; Horch, Elliott P.; Henry, Todd J.; Recons Team (Bulletin of the American Astronomical Society, 2023)
With observations from data sets available to the REsearch Consortium On Nearby Stars (RECONS, http://www.recons.org), we seek to define the orbits of several K dwarf multiple star systems. When compared to their more massive and less massive counterparts in G and M dwarfs, respectively, K dwarfs remain chiefly overlooked, merely due to the scarcity of data obtained on this stellar type. We address the sizes and shapes of the orbits, as established by their periods and eccentricities. The use of system separation, position angle, and magnitude, obtained from both our program measurements and the literature, will allow orbital construction, from which we ultimately derive the fundamental parameter, the mass. This work has been supported by NSF grants AST-1909560 and AST-1910130.
Conference Name: American Astronomical Society Meeting Abstracts ADS Bibcode: 2023AAS...24130243L
Keywords: dept.phy; ⛔ No DOI found

Speckle interferometry at SOAR in 2019 - Tokovinin, Andrei; Mason, Brian D.; Mendez, Rene A.; Costa, Edgardo; Horch, Elliott P. (The Astronomical Journal, 2020)
The results of speckle-interferometric observations at the 4.1 m Southern Astrophysical Research Telescope in 2019 are given, totaling 2555 measurements of 1972 resolved pairs with separations from 15 mas (median 0.″21) and magnitude difference up to 6 mag, and non-resolutions of 684 targets. We resolved for the first time 90 new pairs or subsystems in known binaries. This work continues our long-term speckle program. Its main goal is to monitor orbital motion of close binaries, including members of high-order hierarchies and Hipparcos pairs in the solar neighborhood. We give a list of 127 orbits computed using our latest measurements. Their quality varies from excellent (25 orbits of grades 1 and 2) to provisional (47 orbits of grades 4 and 5). © 2020 The American Astronomical Society. All rights reserved.
20 citations (Crossref) [2023-10-31] tex.ids: tokovininSpeckleInterferometrySOAR2020, tokovininSpeckleInterferometrySoar2020 tex.adsnote: Provided by the SAO/NASA Astrophysics Data System tex.adsurl: https://ui.adsabs.harvard.edu/abs/2020AJ....160....7T arXiv: 2005.05305 [astro-ph.SR] tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85087554458 tex.eid: 7 type: Article
Keywords: 1081; 154; 1777; Astrophysics - Solar and Stellar Astrophysics; Binary stars; Multiple stars; Visual binary stars; dept.phy; peer-reviewed

A Comprehensive Astrometric Calibration of HST's WFPC2. I. Distortion Mapping - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Kozhurina-Platais, Vera; Platais, Imants; Anderson, Jay; Horch, Elliott P. (Publications of the Astronomical Society of the Pacific, 2021)
Wide field planetary camera 2 (WFPC2) exposures are already some 20 years older than Gaia epoch observations, or future James Webb Space Telescope observations. As such, they offer an unprecedented time baseline for high-precision proper-motion studies, provided the full astrometric potential of these exposures is reached. We have started such a project with the work presented here being its first step. We explore geometric distortions beyond the well-known ones published in the early 2000 s. This task is accomplished by using the entire database of WFPC2 exposures in filters F555W, F606W and F814W and three standard astrometric catalogs: Gaia EDR3, 47 Tuc and ωCen. The latter two were constructed using Hubble Space Telescope observations made with cameras other than WFPC2. We explore a suite of centering algorithms, and various distortion maps in order to understand and quantify their performance. We find no high-frequency systematics beyond the 34th-row correction, down to a resolution of 10 pixels. Low-frequency systematics starting at a resolution of 50 pixels are present at a level of 30–50 millipix (1.4–2.3 mas) for the PC and 20–30 millipix (2–3 mas) for the WF chips. We characterize these low-frequency systematics by providing correction maps and updated cubic-distortion coefficients for each filter.
3 citations (Crossref) [2023-10-31]
Keywords: dept.mat; dept.phy; peer-reviewed

A New Home for an Old Hand: The Differential Speckle Survey Instrument Goes to Apache Point - Horch, Elliott P.; Davidson, Jr., James W.; Majewski, Steven R.; Sutherland, Torrie; Shea, Melissa; Henry, Todd J. (Bulletin of the American Astronomical Society, 2023)
The Differential Speckle Survey Instrument (DSSI) was built in 2008 and in its first 14 years saw substantial use in diffraction-limited imaging projects at the WIYN Telescope, Gemini-N and Gemini-S, and the Lowell Discovery Telescope. However, the completion and commissioning of the QWSSI speckle camera at Lowell Observatory has recently created the opportunity to move DSSI to the ARC 3.5-m Telescope at Apache Point Observatory (APO) in New Mexico. We report here on the commissioning of DSSI at APO and discuss some of the early science results, which represent the first diffraction-limited images in the visible range ever obtained at the ARC Telescope. Our initial observations appear to be comparable to DSSI's earlier use at WIYN in that we can obtain 0.05-arcsecond resolution at 692 nm for stars as faint as 12th magnitude in five minutes of observing or less, and we can detect companions with magnitude differences of 4 to 5 relative to their primary stars. In the near term, the instrument will be used (1) to supplement observations for the RECONS K Stars project to survey nearby K dwarfs for companions and (2) to obtain follow-up observations of binaries identified by Kepler, TESS, APOGEE, and other sources. It will also provide a testbed for simultaneous visible and infrared speckle imaging and speckle imaging through coherent fiber bundles. The potential advantages of these two innovations include better photometry in the diffraction-limited regime and higher-quality image reconstructions overall. We gratefully acknowledge support from National Science Foundation grants AST-1909560 and AST-1910130, as well as a SEED grant from the Research Corporation for Science Advancement, in the completion of this work.
Conference Name: American Astronomical Society Meeting Abstracts ADS Bibcode: 2023AAS...24130506H
Keywords: dept.phy; ⛔ No DOI found

Identifying bound stellar companions to kepler exoplanet host stars using speckle imaging - Colton, Nicole M.; Horch, Elliott P; Everett, Mark E; Howell, Steve B; Davidson, James W., Jr.; Baptista, Brian J.; Casetti-Dinescu, Dana I (Astronomical Journal, 2021)
The Kepler mission and subsequent ground-based follow-up observations have revealed a number of exoplanet host stars with nearby stellar companions. This study presents speckle observations of 57 Kepler objects of interest (KOIs) that are also double stars, each observed over a 3-8 yr period, which has allowed us to track their relative motions with high precision. Measuring the position angle and separation of the companion with respect to the primary can help determine if the pair exhibits common proper motion, indicating it is likely to be a bound binary system. We report on the motions of 34 KOIs that have close stellar companions, three of which are triple stars, for a total of 37 companions studied. Eighteen of the 34 systems are confirmed exoplanet hosts, including one triple star, while four other systems have been subsequently judged to be false positives and twelve are yet to be confirmed as planet hosts. We find that 21 are most likely to be common proper motion pairs, 4 are line-of-sight companions, and 12 are of an uncertain disposition at present. The fraction of the confirmed exoplanet host systems that are common proper motion pairs is approximately 86% in this sample. In this subsample, the planets are exclusively found with periods of less than 110 days, so that in all cases the stellar companion is found at a much larger separation from the planet host star than the planet itself. A preliminary period-radius relation for the confirmed planets in our sample suggests no obvious differences at this stage with the full sample of known exoplanets. © 2020. The American Astronomical Society. All rights reserved.
10 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85098523712
Keywords: dept.phy; peer-reviewed

The 24 Aqr triple system: A closer look at its unique high-eccentricity hierarchical architecture - Abushattal, Ahmad A.; Al-Wardat, Mashhoor A.; Horch, Elliott P.; Georgakarakos, Nikolaos; Al-Ameryeen, Hatem A.; Abu-Alrob, Enas M.; Hussein, Abdallah M. (Advances in Space Research, 2023)
As its periastron passage occurred during the third quarter of 2020, system 24 Aqr is of particular significance. New visual solutions for the latest speckle interferometry observations collected by the Lowell Discovery Telescope (LTD) with its new QWSSI speckle camera are presented here. A variety of techniques were used to analyze the system, including ORBITX code for orbital solution, Al-Wardat’s method for analyzing multiple stellar systems, and Edwards’ method for analyzing visual and spectroscopic binaries. We derive precise masses and the complete set of its fundamental parameters for the three components, and we introduce a new orbital solution, and a new dynamical parallax, which is very close to the measured value given by Hipparcos 2007 and from that of Gaia DR2. In the next section, we discuss the possibility of a coplanar orbit. In conclusion, we demonstrate that we need a 65-m telescope to resolve the inner binary visually, although an array of telescopes could be used instead.
Keywords: Atmospheric Modeling-Synthetic Photometry; Hierarchical Triple System; Multiple stars; Observational Astronomy; Spectroscopic Binary Stars; Stars: binaries: close; Visual Binary Stars; dept.phy; peer-reviewed

Speckle observations of TESS exoplanet host stars: Understanding the binary exoplanet host star orbital period distribution - Howell, Steve B; Matson, Rachel A.; Ciardi, David R; Everett, Mark E; Livingston, John H.; Scott, Nicholas J; Horch, Elliott P; Winn, Joshua N (Astronomical Journal, 2021)
We present high-resolution speckle interferometric imaging observations of TESS exoplanet host stars using the NN-EXPLORE Exoplanet and Stellar Speckle Imager instrument at the 3.5 m WIYN telescope. Eight TESS objects of interest that were originally discovered by Kepler were previously observed using the Differential Speckle Survey Instrument. Speckle observations of 186 TESS stars were carried out, and 45 (24%) likely bound companions were detected. This is approximately the number of companions we would expect to observe given the established 46% binarity rate in exoplanet host stars. For the detected binaries, the distribution of stellar mass ratio is consistent with that of the standard Raghavan distribution and may show a decrease in high-q systems as the binary separation increases. The distribution of binary orbital periods, however, is not consistent with the standard Ragahavan model, and our observations support the premise that exoplanet-hosting stars with binary companions have, in general, wider orbital separations than field binaries. We find that exoplanet-hosting binary star systems show a distribution peaking near 100 au, higher than the 40–50 au peak that is observed for field binaries. This fact led to earlier suggestions that planet formation is suppressed in close binaries.
24 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85102449269
Keywords: dept.phy; peer-reviewed

Dissecting the Quadruple Binary Hyad vA 351 Masses for Three M Dwarfs and a White Dwarf\ast - Benedict, G. Fritz; Franz, Otto G.; Horch, Elliott P.; Prato, L.; Torres, Guillermo; McArthur, Barbara E.; Wasserman, Lawrence H.; Latham, David W.; Stefanik, Robert P.; Latham, Christian; Skiff, Brian A. (The Astronomical Journal, 2021)
We extend results first announced by Franz et al., that identified vA 351 = H346 in the Hyades as a multiple star system containing a white dwarf. With Hubble Space Telescope Fine Guidance Sensor fringe tracking and scanning, and more recent speckle observations, all spanning 20.7 years, we establish a parallax, relative orbit, and mass fraction for two components, with a period, and total mass 2.1 . With ground-based radial velocities from the McDonald Observatory Otto Struve 2.1 m Telescope Sandiford Spectrograph, and Center for Astrophysics Digital Speedometers, spanning 37 years, we find that component B consists of BC, two M dwarf stars orbiting with a very short period ( days), having a mass ratio / = 0.95. We confirm that the total mass of the system can only be reconciled with the distance and component photometry by including a fainter, higher-mass component. The quadruple system consists of three M dwarfs (A, B, C) and one white dwarf (D). We determine individual M dwarf masses = 0.53 ± 0.10 , = 0.43 ± 0.04 , and = 0.41 ± 0.04 . The white dwarf mass, 0.54 ± 0.04 , comes from cooling models, an assumed Hyades age of 670 Myr, and consistency with all previous and derived astrometric, photometric, and radial velocity results. Velocities from Hα and He i emission lines confirm the BC period derived from absorption lines, with similar (He i) and higher (Hα) velocity amplitudes. We ascribe the larger Hα amplitude to emission from a region each component shadows from the other, depending on the line of sight.
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Speckle imaging characterization of radial velocity exoplanet systems - Dalba, Paul A.; Kane, Stephen R.; Howell, Steve B; Horch, Elliott P; Li, Zhexing; Hirsch, Lea A.; Burt, Jennifer; Brandt, Timothy D.; Močnik, Teo; Henry, Gregory W. (Astronomical Journal, 2021)
We conducted speckle imaging observations of 53 stellar systems that were members of long-term radial velocity (RV) monitoring campaigns and exhibited substantial accelerations indicative of planetary or stellar companions in wide orbits. Our observations were made with blue and red filters using the Differential Speckle Survey Instrument at Gemini-South and the NN-Explore Exoplanet Stellar Speckle Imager at the WIYN telescope. The speckle imaging identifies eight luminous companions within 2" of the primary stars. In three of these systems-HD 1388, HD 87359, and HD 104304-the properties of the imaged companion are consistent with the RV measurements, suggesting that these companions may be associated with the primary and the cause of the RV variation. For all 53 stellar systems, we derive differential magnitude limits (i.e., contrast curves) from the imaging. We extend this analysis to include upper limits on companion mass in systems without imaging detections. In 25 systems, we rule out companions with masses greater than 0.2 M⊙, suggesting that the observed RV signals are caused by late-M dwarfs or substellar (potentially planetary) objects. On the other hand, the joint RV and imaging analysis almost entirely rules out planetary explanations of the RV signal for HD 19522 and suggests that the companion must have an angular separation below a few tenths of an arcsecond. This work highlights the importance of combined RV and imaging observations for characterizing the outer regions of nearby planetary systems. © 2021 Institute of Physics Publishing. All rights reserved.
5 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101618449
Keywords: dept.phy; peer-reviewed

The POKEMON Speckle Survey of nearby M Dwarfs. II. Observations of 1125 targets - Clark, Catherine A.; Belle, Gerard T. van; Horch, Elliott P.; Lund, Michael B.; Ciardi, David R.; Braun, Kaspar von; Winters, Jennifer G.; Everett, Mark E.; Hartman, Zachary D.; Llama, Joe (The Astronomical Journal, 2024)
Stellar multiplicity is correlated with many stellar properties, yet multiplicity measurements have proven difficult for the M dwarfs—the most common type of star in our galaxy—due to their faintness and the fact that a reasonably complete inventory of later M dwarfs did not exist until recently. We have therefore carried out the Pervasive Overview of “Kompanions” of Every M dwarf in Our Neighborhood (POKEMON) survey, which made use of the Differential Speckle Survey Instrument on the 4.3 m Lowell Discovery Telescope, along with the NN-EXPLORE Exoplanet Stellar Speckle Imager on the 3.5 m WIYN telescope. The POKEMON sample is volume limited from M0V through M9V out to 15 pc, with additional brighter targets at larger distances. In total, 1125 targets were observed. New discoveries were presented in the first paper in the series. In this second paper in the series, we present all detected companions, gauge our astrometric and photometric precision, and compare our filtered and filterless speckle observations. We find that the majority (58.9%) of the companions we detect in our speckle images are not resolved in Gaia, demonstrating the need for high-resolution imaging in addition to long-term astrometric monitoring. Additionally, we find that the majority (73.2%) of simulated stellar companions would be detectable by our speckle observations. Specifically within 100 au, we find that 70.3% of simulated companions are recovered. Finally, we discuss future directions of the POKEMON survey.
Keywords: dept.phy; peer-reviewed

Solar System Realms: Stars Taking Up Space Where Planets Could Be - Henry, Todd J.; Paredes, Leonardo A.; Vrijmoet, Eliot; Couperus, Andrew C.; James, Hodari-Sadiki; Jao, Wei-Chun; Kar, Aman; Lesley, DeAndre X.; Casetti-Dinescu, Dana I.; Horch, Elliott P.; Winters, Jennifer G. (2021)
The RECONS (REsearch Consortium On Nearby Stars, www.recons.org) team continues to explore the solar neighborhood by evaluating the nearest stars, both individually and as a population. Key points are becoming clear: we now know that 86% of all stars are K and M dwarfs, and we need to reach to 50 pc and 25 pc, respectively, to create samples of 5000 and 3000 primaries each. These two sizable samples allow us to understand the outcome of the star formation process across a factor of ten in mass as never before. Here we focus on one crucial area of research — stellar companions — with results of our surveys combining radial velocities, astrometry, high-resolution imaging, and trawls of catalogs and the literature. The surveys are carried out primarily at the CTIO/SMARTS 0.9m and 1.5m, the SOAR 4.1m, and both Gemini 8.1m telescopes. We reveal companions at separations from less than 1 AU to more than 1000 AU from the K and M dwarfs, with the key result that these stellar partners are found most often at separations similar to our Solar System. Thus, the star and planet formation processes work on the same spatial scales ... a fact that we must keep in mind as our solar neighborhood becomes enriched with planetary discoveries at distances comparable to where stellar companions are found. This work has been supported by NSF grants AST-0507711, AST-0908402, AST-1109445, AST-1411206, and AST-1715551, AST-1910130, and the SMARTS Consortium.
Conference Name: The 20.5th Cambridge Workshop on Cool Stars, Stellar Systems, and the Sun (CS20.5) Pages: 183 ADS Bibcode: 2021csss.confE.183H
Keywords: K dwarf stars (876) M dwarf stars (982) Multiple stars (1081) Stellar populations (1622); dept.phy

Observations with the differential speckle survey instrument. X. Preliminary orbits of k-dwarf binaries and other stars - Horch, Elliott P.; Broderick, Kyle G.; Casetti-Dinescu, Dana I.; Henry, Todd J.; Fekel, Francis C.; Muterspaugh, Matthew W.; Willmarth, Daryl W.; Winters, Jennifer G.; van Belle, Gerard T.; Clark, Catherine; Everett, Mark E. (The Astronomical Journal, 2021)
This paper details speckle observations of binary stars taken at the Lowell Discovery Telescope, the WIYN telescope, and the Gemini telescopes between 2016 January and 2019 September. The observations taken at Gemini and Lowell were done with the Differential Speckle Survey Instrument (DSSI), and those done at WIYN were taken with the successor instrument to DSSI at that site, the NN-EXPLORE Exoplanet Star and Speckle Imager (NESSI). In total, we present 378 observations of 178 systems, and we show that the uncertainty in the measurement precision for the combined data set is ∼2 mas in separation, ∼1°-2° in position angle depending on the separation, and ∼0.1 mag in magnitude difference. Together with data already in the literature, these new results permit 25 visual orbits and one spectroscopic-visual orbit to be calculated for the first time. In the case of the spectroscopic-visual analysis, which is done on the ternary star HD 173093, we calculate masses with a precision of better than 1% for all three stars in that system. Twenty-one of the visual orbits calculated have a K dwarf as the primary star; we add these to the known orbits of K-dwarf primary stars and discuss the basic orbital properties of these stars at this stage. Although incomplete, the data that exist so far indicate that binaries with K-dwarf primaries tend not to have low-eccentricity orbits at separations of one to a few tens of astronomical units, that is, on solar system scales. © 2021 Institute of Physics Publishing. All rights reserved.
6 citations (Crossref) [2023-10-31] https://par.nsf.gov/biblio/10296367-observations-differential-speckle-survey-instrument-preliminary-orbits-dwarf-binaries-other-stars ; https://ui.adsabs.harvard.edu/abs/2021AJ....161..295H/abstract ;
Keywords: dept.phy; peer-reviewed

Twin High-Resolution, High-Speed Imagers for the Gemini Telescopes: Instrument Description and Science Verification Results - Scott, Nicholas J.; Howell, Steve B.; Gnilka, Crystal L.; Stephens, Andrew W.; Salinas, Ricardo; Matson, Rachel A.; Furlan, Elise; Horch, Elliott P.; Everett, Mark E.; Ciardi, David R.; Mills, Dave; Quigley, Emmett A. (Frontiers in Astronomy and Space Sciences, 2021)
Two new imaging instruments, ‘Alopeke and Zorro, were designed, built, and commissioned at the Gemini-North and Gemini-South telescopes in 2018 and 2019, respectively. Here we describe them and present the results from over a year of operation. The two identical instruments are based on the legacy of the DSSI (Differential Speckle Survey Instrument) instrument, successfully used for years at the WIYN and the Gemini telescopes in Hawaii and Chile. ‘Alopeke and Zorro are dual-channel imagers having both speckle (6.7″) and “wide-field” (∼1 arcminute) field-of-view options. They were built to primarily perform speckle interferometry providing diffraction-limited imagery at optical wavebands, yielding pixel scale uncertainties of ±0.21 mas, position angle uncertainties of ±0.7◦, and photometric uncertainties of Δm ± 0.02–0.04 magnitudes (for the blue and red channels, respectively) when run through the standard data reduction pipeline. One of their main scientific roles is the validation and characterization of exoplanets and their host stars as discovered by transit surveys such as the NASA Kepler, K2, and TESS missions. The limiting magnitude for speckle observations at Gemini can be quite faint (r ∼18 in good observing conditions) but typically the observed targets are brighter. The instruments can also function as conventional CCD imagers providing a 1 arc-minute field of view and allowing simultaneous two-color, high-speed time-series operation. These resident visitor instruments are remotely operable and are available for use by the community via the peer-reviewed proposal process.
50 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Observations with the Differential Speckle Survey Instrument. XI. First uear of observations from Apache Point Observatory - Davidson, James W.; Horch, Elliott P.; Majewski, Steven R.; Fagan, Evan; Shea, Melissa A.; Sutherland, Torrie; Wilson, Robert F.; Lesley, D. Xavier; Pellegrino, Richard A.; Leonard, Jonathan P.; Wilson, John C.; Chanover, Nancy J.; et al. (The Astronomical Journal, 2024)
The Differential Speckle Survey Instrument (DSSI) was relocated to the Astrophysical Research Consortium 3.5 m telescope at Apache Point Observatory (APO) in early 2022. Here we present results from the first year of observations along with an updated instrument description for DSSI at APO, including a detailed description of a new internal slit mask assembly used to measure the instrument plate scale from first principles. Astrometric precision for DSSI at APO during this time was measured to be 2.06 ± 0.11 mas, with a photometric precision of 0.14 ± 0.04 mag. Results of 40 resolved binary systems are reported, including two that were previously unknown to be binaries: HIP 7535 and HIP 9603. We also present updated orbital fits for two systems: HIP 93903 and HIP 100714. Finally, we report updated or confirmed dispositions for five Kepler Objects of Interest (KOIs) that were previously explored in Colton et al., using speckle imaging to discern common proper motions pairs from line of sight companions: KOI-270, KOI-959, KOI-1613, KOI-1962, and KOI-3214AB.
Keywords: dept.phy

Observations of binary stars with the differential speckle survey instrument. IX. Observations of known and suspected binaries, and a partial survey of be stars - Horch, Elliott P.; van Belle, Gerard T.; Davidson, James W., Jr.; Willmarth, Daryl; Fekel, Francis C.; Muterspaugh, Matthew; Casetti-Dinescu, Dana I.; Hahne, Frederick W.; Granucci, Nicole M.; Clark, Catherine; Winters, Jennifer G.; Rupert, Justin D.; et al. (The Astronomical Journal, 2020)
We report 370 measures of 170 components of binary and multiple-star systems, obtained from speckle imaging observations made with the Differential Speckle Survey Instrument at Lowell Observatory's Discovery Channel Telescope in 2015 through 2017. Of the systems studied, 147 are binary stars, 10 are seen as triple systems, and 1 quadruple system is measured. Seventy-six high-quality nondetections and 15 newly resolved components are presented in our observations. The uncertainty in relative astrometry appears to be similar to our previous work at Lowell, namely, linear measurement uncertainties of approximately 2 mas, and the relative photometry appears to be uncertain at the 0.1-0.15 mag level. Using these measures and those in the literature, we calculate six new visual orbits, including one for the Be star 66 Oph and two combined spectroscopic-visual orbits. The latter two orbits, which are for HD 22451 (YSC 127) and HD 185501 (YSC 135), yield individual masses of the components at the level of 2% or better, and independent distance measures that in one case agrees with the value found in the Gaia DR2 and in the other disagrees at the 2σ level. We find that HD 22451 consists of an F6V+F7V pair with orbital period of 2401.1 ± 3.2 days and masses of 1.342 ± 0.029 and 1.236 ± 0.026M⊙. For HD 185501, both stars are G5 dwarfs that orbit one another with a period of 433.94 ± 0.15 days, and the masses are 0.898 ± 0.012 and 0.876 ± 0.012M⊙ . We discuss the details of both the new discoveries and the orbit objects. © 2020. The American Astronomical Society. All rights reserved..
17 citations (Crossref) [2023-10-31] tex.ids: horchObservationsBinaryStars2020a tex.adsnote: Provided by the SAO/NASA Astrophysics Data System tex.adsurl: https://ui.adsabs.harvard.edu/abs/2020AJ....159..233H arXiv: 2004.03065 [astro-ph.SR] tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086596087 tex.eid: 233 type: Article
Keywords: Astrophysics - Earth and Planetary Astrophysics; Astrophysics - Instrumentation and Methods for Astrophysics; Astrophysics - Solar and Stellar Astrophysics; dept.phy; peer-reviewed

The orbit and dynamical mass of polaris: Observations with the CHARA array - Evans, Nancy Remage; Schaefer, Gail H.; Gallenne, Alexandre; Torres, Guillermo; Horch, Elliott P.; Anderson, Richard I.; Monnier, John D.; Roettenbacher, Rachael M.; Baron, Fabien; Anugu, Narsireddy; Davidson, James W.; Kervella, Pierre; et al. (The Astrophysical Journal, 2024)
The 30 yr orbit of the Cepheid Polaris has been followed with observations by the Center for High Angular Resolution Astronomy (CHARA) Array from 2016 through 2021. An additional measurement has been made with speckle interferometry at the Apache Point Observatory. Detection of the companion is complicated by its comparative faintness—an extreme flux ratio. Angular diameter measurements appear to show some variation with pulsation phase. Astrometric positions of the companion were measured with a custom grid-based model-fitting procedure and confirmed with the CANDID software. These positions were combined with the extensive radial velocities (RVs) discussed by Torres to fit an orbit. Because of the imbalance of the sizes of the astrometry and RV data sets, several methods of weighting are discussed. The resulting mass of the Cepheid is 5.13 ± 0.28 M ⊙. Because of the comparatively large eccentricity of the orbit (0.63), the mass derived is sensitive to the value found for the eccentricity. The mass combined with the distance shows that the Cepheid is more luminous than predicted for this mass from evolutionary tracks. The identification of surface spots is discussed. This would give credence to the identification of a radial velocity variation with a period of approximately 120 days as a rotation period. Polaris has some unusual properties (rapid period change, a phase jump, variable amplitude, and unusual polarization). However, a pulsation scenario involving pulsation mode, orbital periastron passage, and low pulsation amplitude can explain these characteristics within the framework of pulsation seen in Cepheids.
Keywords: dept.phy; peer-reviewed

JWST/NIRCam 4–5 μm Imaging of the Giant Planet AF Lep b - Franson, Kyle; Balmer, William O.; Bowler, Brendan P.; Pueyo, Laurent; Zhou, Yifan; Rickman, Emily; Zhang, Zhoujian; Mukherjee, Sagnick; Pearce, Tim D.; Gagliuffi, Daniella C. Bardalez; Biddle, Lauren I.; Brandt, Timothy D.; et al. (The Astrophysical Journal Letters, 2024)
With a dynamical mass of 3 M Jup, the recently discovered giant planet AF Lep b is the lowest-mass imaged planet with a direct mass measurement. Its youth and spectral type near the L/T transition make it a promising target to study the impact of clouds and atmospheric chemistry at low surface gravities. In this work, we present JWST/NIRCam imaging of AF Lep b. Across two epochs, we detect AF Lep b in F444W (4.4 μm) with signal-to-noise ratios of 9.6 and 8.7, respectively. At the planet’s separation of 320 mas during the observations, the coronagraphic throughput is ≈7%, demonstrating that NIRCam’s excellent sensitivity persists down to small separations. The F444W photometry of AF Lep b affirms the presence of disequilibrium carbon chemistry and enhanced atmospheric metallicity. These observations also place deep limits on wider-separation planets in the system, ruling out 1.1 M Jup planets beyond 15.6 au (0.″58), 1.1 M Sat planets beyond 27 au (1″), and 2.8 M Nep planets beyond 67 au (2.″5). We also present new Keck/NIRC2 imaging of AF Lep b; combining this with the two epochs of F444W photometry and previous Keck photometry provides limits on the long-term 3–5 μm variability of AF Lep b on timescales of months to years. AF Lep b is the closest-separation planet imaged with JWST to date, demonstrating that planets can be recovered well inside the nominal (50% throughput) NIRCam coronagraph inner working angle.
Keywords: dept.phy

HAT-P-68b: A transiting hot jupiter around a K5 dwarf star - Lindor, Bethlee M.; Hartman, Joel D.; Bakos, Gáspár Á.; Bhatti, Waqas; Csubry, Zoltan; Penev, Kaloyan; Bieryla, Allyson; Lathman, David W; Torres, Guillermo; Buchhave, Lars A; de Val-Borro, Miguel; Howard, Andrew W; et al. (Astronomical Journal, 2021)
We report the discovery by the ground-based Hungarian-made Automated Telescope Network (HATNet) survey of the transiting exoplanet HAT-P-68b, which has a mass of 0.724 ± 0.043 MJ, and radius of 1.072 ± 0.012 RJ. The planet is in a circular P = 2.2984 day orbit around a moderately bright V = 13.937 ± 0.030 magnitude K-dwarf star of mass ${0.673}_{-0.014}{+0.020}$ M⊙, and radius 0.6726 ± 0.0069 R⊙. The planetary nature of this system is confirmed through follow-up transit photometry obtained with the Fred L. Whipple Observatory (FLWO) 1.2 m telescope, high-precision radial velocities measured using Keck I/High Resolution Echelle Spectrometer (HIRES), FLWO 1.5 m/Tillinghast Reflector Echelle Spectrograph (TRES), and Observatoire de Haute-Provence (OHP) 1.9 m/Sophie, and high-spatial-resolution speckle imaging from WIYN 3.5 m/DSSI. HAT-P-68 is at an ecliptic latitude of +3° and outside the field of view of both the NASA Transiting Exoplanet Survey Satellite primary mission and the K2 mission. The large transit depth of 0.036 mag (r band) makes HAT-P-68b a promising target for atmospheric characterization via transmission spectroscopy.
2 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101652867
Keywords: dept.phy; peer-reviewed

HAT-P-58b – HAT-P-64b: Seven planets transiting bright stars - Bakos, G. Á.; Hartman, Joel D.; Bhatti, Waqas; Csubry, Z.; Penev, Kaloyan; Bieryla, Allyson; Latham, D. W.; Quinn, S. N.; Buchhave, Lars A.; Kovács, Gábor L.; Torres, Guillermo; Noyes, R. W.; et al. (The Astronomical Journal, 2021)
We report the discovery and characterization of seven transiting exoplanets from the HATNet survey. The planets, which are hot Jupiters and Saturns transiting bright Sun-like stars, include: HAT-P-58b (with mass M p = 0.37 M J, radius R p = 1.33 R J, and orbital period P = 4.0138 days), HAT-P-59b (M p = 1.54 M J, R p = 1.12 R J, P = 4.1420 days), HAT-P-60b (M p = 0.57 M J, R p = 1.63 R J, P = 4.7948 days), HAT-P-61b (M p = 1.06 M J, R p = 0.90 R J, P = 1.9023 days), HAT-P-62b (M p = 0.76 M J, R p = 1.07 R J, P = 2.6453 days), HAT-P-63b (M p = 0.61 M J, R p = 1.12 R J, P = 3.3777 days), and HAT-P-64b (M p = 0.58 M J, R p = 1.70 R J, P = 4.0072 days). The typical errors on these quantities are 0.06 M J, 0.03 R J, and 0.2 s, respectively. We also provide accurate stellar parameters for each of the host stars. With V = 9.710 0.050 mag, HAT-P-60 is an especially bright transiting planet host, and an excellent target for additional follow-up observations. With R p = 1.703 0.070 R J, HAT-P-64b is a highly inflated hot Jupiter around a star nearing the end of its main-sequence lifetime, and is among the largest known planets. Five of the seven systems have long-cadence observations by TESS which are included in the analysis. Of particular note is HAT-P-59 (TOI-1826.01) which is within the northern continuous viewing zone of the TESS mission, and HAT-P-60, which is the TESS candidate TOI-1580.01. © 2021. The American Astronomical Society. All rights reserved..
5 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed